Risk Preferences, Shocks and Technology Adoption: Farmers' Responses to Drought Risk - Stein T. Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2015)
Climate risk represents an increasing threat to poor and vulnerable farmers in drought-prone areas of Africa. This study assesses the maize and fertilizer adoption responses of food insecure farmers in Malawi, where Drought Tolerant (DT) maize was recently introduced. A field experiment, eliciting relative risk aversion, loss aversion and subjective probability weighting parameters of farmers, is combined with a detailed farm household survey that measured the intensity of adoption of different maize types and fertilizer use on the different maize types and recorded exposure to past and present drought and other shocks. More risk averse households were more likely to have adopted DT maize, less likely to have adopted other improved maize varieties and less likely to have dis-adopted traditional local maize. Exposure to past drought shocks stimulated adoption of DT maize and dis-adoption of local maize. Over-weighting of small probabilities was associated with less use of fertilizer on all maize types.
Keywords: C93; D03; O33; Q12; Q18; 330; Drought risk; shocks; risk aversion; subjective probability weighting; loss aversion; technology adoption; adaptation; Cragg model; maize; Drought Tolerant maize; fertilizer use